REPRESENTASI PENERAPAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN SANITASI, HIGIENE DAN KESEHATAN KESELAMATAN KERJA DI SMK - Aldina Putri Rizkia; Anggri Sekar Sari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
Research aims to representation the application of audio-visual media including planning, implementation and evaluation, inhibiting and supporting factors. This type of research is qualitative. Data collection: interviews, observation, documentation. The validity of the data uses triangulation techniques. Data analysis techniques: data collection, data reduction, data presentation, data verification. The results of the study (1) the application of audio-visual media include: planning carried out well, audio-visual media contained in the RPP, the implementation has been carried out quite well, the infrastructure facilities in the classroom are inadequate, the evaluation has been carried out quite well, the end of the questioning but evaluation of the use of audio visual media has not been implemented. (2) Factors supporting the easy access of the internet to obtain material and the inhibiting factors for the use of audio-visual media are inadequate infrastructure.Â